Políticas Crediticias de la Comercializadora ILE S.A. - Rodríguez Perero, Jessenia Gabriela (2018)
The Comercializadora ILE S.A. starts its activities in 1972 in the city of Loja being a small and traditional condiment factory, having as main products of manufacture and marketing: cumin, ground pepper, rehash and flavor, 100% natural seasoning that are sold regionally, having as a mission to generate food solutions, aimed at the satisfaction of global customers and consumers, innovating processes, contributing in a sustainable way to the development of a more prosperous society friendly with the environment. The present investigation analyzes the margin of sales and collections that each seller has where the person responsible for the company performs the portfolio analysis to verify values ​​reflected in the invoices and annexes, presenting as results of that analysis an activity called "jineteo" which leads to legal proceedings. One of the research techniques used was the interview aimed at complying with the company's policies, which is based on the internal regulations, in order to know if they are fully met; taking into account that all the necessary documents are available for verification, which will allow obtaining the necessary information. This case study complies with the research sublines of the Engineering in Accounting and Audit which is the accounting information management model in relation to the study of the past due portfolio and its liquidity in terms of credit sales, for be applied to the credit policies of the Comercializadora ILE SA; Being a company that is dedicated to the production and marketing of high quality food.